2023
DOI: 10.1136/bcr-2023-254660
|View full text |Cite
|
Sign up to set email alerts
|

Laterally extended endopelvic resection as part of the surgical management of disseminated retroperitoneal leiomyomatosis mimicking low-grade sarcoma in a patient with a solitary kidney

Abstract: Leiomyomas are common benign uterine smooth muscle tumours. Rarer subsets may demonstrate aggressive extrauterine growth which mimic metastatic disease. We discuss the case of a female patient in her 40s, with a long-standing atrophic right kidney, presenting with a 17 cm uterine mass demonstrating bilateral para-aortic and pelvic sidewall spread. Although biopsies favoured the diagnosis of a benign tumour, a leiomyosarcoma could not be excluded. The surgical complexity of the case was compounded by a tumour r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer [17][18][19][20][21][22][23][24][25]. Achieving resection of all macroscopic disease (R0) is the single independent factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer [17][18][19][20][21][22][23][24][25]. Achieving resection of all macroscopic disease (R0) is the single independent factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Until new treatments options are identified, surgery with maximal cytoreductive effort remains the mainstay treatment for this histological subtype of ovarian cancer. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Achieving resection of all macroscopic disease (R0) is the single independent factor for survival. In their meta‐analysis including 6885 patients with advanced ovarian cancer, Bristow et al (2023) have shown there is a 5.5% increase in median survival time with each 10% increase in maximal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…These complications were managed by further procedures alongside years of antibiotics and immunosuppressants without success, and still further exacerbated by delays in treatment, as teams were hesitant to intervene on such a hostile abdomen. This highlights the paradigm of surgical challenge in Crohn's disease wherein the disease complicates the surgery and the surgery complicates the disease 4 . This case highlights how a disease that is assumed to largely affect the gastric system can go on to cause dysfunction across the bio‐psychosocial health of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the paradigm of surgical challenge in Crohn's disease wherein the disease complicates the surgery and the surgery complicates the disease. 4 This case highlights how a disease that is assumed to largely affect the gastric system can go on to cause dysfunction across the bio-psychosocial health of an individual. Finally, our successful management of this case identifies how definitive treatment is often necessary to improve a patient's quality of life and how a multidisciplinary approach is needed to provide such treatment.…”
Section: A S E Pr E S E Ntati O Nmentioning
confidence: 99%